Parent’s confidence level as a caregiver towards their infants in neonatal intensive care unit (nicu) at Hospital Universiti Sains Malaysia (Hospital USM) - Kamarudzaman, Nur Husnina Atiqah (Universiti Sains Malaysia, 2013)
Admission of infant into Neonatal Intensive Care Unit (NICU) interrupts the attachment process of parents and their baby. The opportunity for parents to give care to their infant will be limited as their infant need intensive care from the nurse to overcome their health problem. As the result, it will affect the confidence level of parents to handle the infant. The purpose of this study is to identify parent’s level of confidence during performing infant care (medication administration, bathing, holding, feeding regimens, monitoring devices and recognizing changes in the infant’s health status) prior discharge from NICU at Hospital USM. A convenience sample of 42 parents that have infants admitted into NICU at Hospital USM were included in the study. Data was collected using sociodemographic data and 38 items of Transition Questionnaire (Kenner, 1994). The test results revealed there were no association between educational level and parents confidence level with p 0.05 (p = 0.364). Also, analysis of association between psychosocial status and parents’ confidence revealed no statistical difference (p> 0.05). This study suggested that nurses working in neonatal intensive care units need to construct nursing care around the parents especially for mother- infant bonding, with roles and responsibilities that incorporate support of increase the confidence level of parents to handle their infant that admit to NICU.